Value Clarification Technique Model Assisted by Media Board Game on Nationality Attitudes of Elementary School - Putri, Ni Kadek Bintang Yulinda; Wulandari, I Gusti Agung Ayu; Agetania, Ni Luh Putu (Universitas Pendidikan Ganesha, 2024)
The lack of teacher skills in building students' character in the Pancasila education subject impacts the decline in students' attitudes. A common decline in attitude is seen when students are not fully attentive during the flag-raising ceremony and do not display proper posture while singing national anthems. To address this issue, a learning model is needed to enhance students' national attitudes. This study aims to examine the effect of the Value Clarification Technique (VCT) learning model assisted by board game media on national attitudes in the Pancasila education subject among fourth-grade elementary school students. This research is a quasi-experimental study using a non-equivalent post-test-only control group design. The population consists of 195 fourth-grade elementary school students. The sample was selected using cluster random sampling, with 28 students in the experimental group and 28 students in the control group. Data collection was conducted through observation using observation sheets as the instrument. The research data were analyzed using inferential statistics (t-test). Based on the hypothesis testing through t-test calculation at a significance level (α) of 0.05, the results showed tcount=3.920 and ttable=1.674t. Since tcount>ttable, H0 is rejected, and H1 accepted. These results indicate a significant effect of applying the Value Clarification Technique (VCT) learning model assisted by board game media on students' national attitudes. This research implies that the learning process can be more effective and efficient in instilling national values to students. This is expected to help students develop a national attitude that is in line with the expectations and goals of education.